Extensive coil embolization of a giant coronary artery aneurysm in an octogenarian: a case report. Issue 3 (3rd May 2020) - Ahmed, Talha; Chahal, Diljon; Shkullaku, Melsjan; Gupta, Anuj
Abstract: Background: Coronary artery aneurysms (CAA) are often diagnosed incidentally on coronary angiography or imaging modalities done for other reasons. 'Giant' CAA by definition exceeds 20 mm in diameter or four times the diameter of normal coronary artery. The management of patients with CAAs is challenging due to poorly understood mechanism, variable presentation, and lack of clear-cut societal recommendations. Though conservative management is preferred in asymptomatic patients, massive size or interval growth may make intervention necessary. Case summary: We describe a case of successful coil embolization of a giant coronary aneurysm in an elderly 84-year-old male. Patient, who presented for a follow-up computed tomography angiography to evaluate a previously repaired abdominal aortic aneurysm 2 years back, was found to have interval growth of right coronary artery aneurysm from 4 cm in diameter to 7 × 8 cm in its greatest dimensions. The rationale for treatment was to prevent sudden death from continued growth and eventual rupture of aneurysm in addition to potential risk of thromboembolism and compression of adjacent structures. Discussion: This case demonstrates the safe and successful use of extensive coil embolization technique to treat a 'giant' CAA in an elderly patient when surgical risks were prohibitive.